SAT0576 Associations between Five Important Domains of Health and The Patient Acceptable Symptom State in Rheumatoid Arthritis and Psoriatic Arthritis: A Cross Sectional Study of 977 Patients. (15th July 2016) - Puyraimond-Zemmour, D.; Etcheto, A.; Fautrel, B.; Balanescu, A.; de Wit, M.; Heiberg, T.; Otsa, K.; Kvien, T.K.; Dougados, M.; Gossec, L.
Abstract : Background: The objectives of treatments in rheumatoid arthritis (RA) and psoriatic arthritis (PsA) include acceptable quality of life from the patient's perspective. One simple question can be used to evaluate the level of acceptability of the disease status by a patient: the patient acceptable symptom state (PASS) which corresponds to the concept of "feeling well". Objectives: The objective was to explore the link between a patient acceptable symptom state (PASS) and patient-perceived impact in rheumatoid arthritis (RA) and psoriatic arthritis (PsA). Methods: Cross-sectional study of unselected patients with definite RA or PsA. Five domains of health were analysed: Pain, functional capacity, fatigue, coping and sleep disturbance. They were assessed by a numeric rating scale (0–10) and were compared between patients in PASS or not (Cohen's effect sizes). The domains of health associated with PASS status were assessed by multivariate logistic regression, and PASS thresholds were determined using the 75th percentile method and ROC analyses. Results: Among 977 patients (531 RA, 446 PsA) mean age was 53.4±13.2 yrs; mean disease duration was 11.2±10.0 yrs; 637 (65.8%) were females. In all, 595 patients (60.9%) were in PASS: they had lower symptom levels, and all domains of health except sleep disturbance discriminated clearly between patients in PASS or not (effect sizes, 0.73 to 1.45 in RA and 0.82 to 1.41 in PsA). In multivariate analyses, pain and coping were predictive of not being in PASS: odds ratio [95% confidence interval] 0.81 [0.67–0.96] and 0.63 [0.52–0.75] for pain and 0.84 [0.74–0.96] and 0.83 [0.71–0.97] for coping, in RA and PsA respectively. The cut-offs of symptom intensity (range 0–10) corresponding to PASS for the five domains of health and the two diseases with a score were similar, i.e. around 4–5. Conclusions: Two thirds of 977 unselected tertiary care patients with rheumatoid arthritis (RA) or psoriatic arthritis (PsA) were in PASS. In RA and PsA, PASS was associated with the five domains of health analysed, and in particular with less pain and better coping. PASS levels in the two diseases for the five domains of health, as well as the RAID and PsAID scores were similar with cut-offs around 4–5 points (0–10 scale). References: Gossec L. et al, Ann Rheum Dis, 2014. Gossec L. et al, Ann Rheum Dis 2009. Disclosure of Interest: None declared